(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
A complicated public health problem is elder abuse. This study’s objective is to give a succinctsummary of elder abuse in India among individuals 60 and older at the national and state levels. The majorgoal of this study is to analyse the frequency and causes of elder abuse in light of the most recent dataavailable, with a focus on older individuals’ employment status. We also look at the relative significance ofunique elements that contribute to the gender differences in elder abuse. Additionally, this study offerssome solutions for the issue of elder abuse. Although the overall prevalence of elder abuse in India is verylow (5.22), data from the 2020 Longitudinal Ageing Study in India show that there are significant statelevelvariances. In comparison to men, women, working older persons (particularly working women),people under the age of 70, people with more household assets, people who aren’t married, people wholive in rural regions, and those who aren’t in good health have significantly higher odds of being abused.To stop abuse, income and education must both reach a crucial point. The gender discrepancy in theprevalence of elder abuse is only 10 explained by differences in economic conditions.